Seasonal algal blooms support sediment release of phosphorus via positive feedback in a eutrophic lake: Insights from a nutrient flux tracking modeling - Zou, Rui; Wu, Zhen; Zhao, Lei; Elser, James J.; Yu, Yanhong; Chen, Yihui; Liu, Yong (Ecological modelling, 2020)
[Display omitted] •A water quality modeling–based flux tracking approach was proposed for budgets analysis.•Increasing N and P benthic fluxes supported internal loading that inhibited lake restoration.•N loading reduction is more efficient than P for Lake Dianchi rehabilitation.•A positive feedback is detected between algal blooms and benthic P flux. Despite the great effort of nutrient loading reduction, lake rehabilitation often suffers from the impacts of internal nutrient cycling. However, the mechanisms of internal nutrient cycling, specifically the feedback of algal blooms on nutrients cycling is still an open question. Management of Lake Dianchi, the most eutrophic lake in China, has involved a series of costly measures but without significant algal bloom decreasing. In view of the difficulty to evaluate the importance of internal cycling only by monitoring data, a three-dimensional model-based flux tracking approach was performed to identify the contributions of internal cycling. The results highlighted the role of nitrogen (N) and phosphorus (P) benthic fluxes with high seasonal fluctuations, contributing ∼29 %(N) and ∼18 %(P) of total input. The scenario analysis indicated that N loading reduction was more efficient for lake restoration. Furthermore, A positive feedback was detected between algae biomass and benthic P flux. Benthic P flux varied from adsorption to release when algae biomass increased. This phenomenon implied that a close link existed between N and P cycles with algae acting as a strong integrator. Due to the positive feedback loop between benthic P flux and algal blooms as well as the high efficiency of N loading reduction, controlling both N and P loadings will benefit lake restoration, especially eutrophic lakes with heavy sediment nutrient loadings.